Evagrius Copticus - Pierre l'Apotre ou Pierre d'Alexandrie - L'homelie copte acephale en l'honneur des XXIV Vieillards - Lucchesi, Enzo (Analecta Bollandiana, 1999)
The Coptic fragment M 664B(41) in the Pierpont Morgan Library, New York, because of the name of Peter has been classified among the apocryphal Acts of the Apostles but for codicological reasons is probably part of the Panegyric of Peter of Alexandria by Alexander, the Sahidic recension of which is only preserved in fragmentary form.